Plasma surface modification of polycarbonate and polypropylene substrates for biomedical electrodes - Pedrosa, P. (2010)
The effects of surface plasma treatments on the properties of PP and PC substrates were studied. Main results showed that the 0.48 Pa Ar treatment promoted the most favorable changes: roughness increased from 15 to 17 nm for PC and from 12 to 30 nm for PP, while the CA lowered from 958 to 598 and from 878 to 358 for PC and PP, respectively. The effects of the activation treatment on adhesion were checked by depositing a thin layer of TiN on both untreated and 0.48 Pa Ar plasma treated PC samples, and the adhesion to both substrates compared using the standard X-cut tape test. The Ar activated samples displayed better adhesion of the TiN film than the untreated ones, confirming the benefits of the surface changes induced by the plasma treatments.